As sutilezas metafísicas e manhas teológicas da economia política: contribuições da crítica feuerbachiana da religião para a crítica da economia e da política em Karl Marx - Ariza, Péricles (2023)
This thesis seeks to deepen the understanding of the structural assumptions of the capitalist mode of production through a study of the relationship and argumentative analogy that exists, according to Feuerbach and Marx respectively, between the criticism of theology and Political Economy. We therefore highlight the analogous structure of the process of alienation and estrangement of man from himself and his own essence, as well as from nature itself. The alienated work and estrangement caused by the capitalist mode of production, based on private property, that is, on the separation of the worker from himself, his product, his creation, causes it to assume an autonomous, fetishizing form and, therefore, Even religious. Therefore, the present work aims to problematize the following questions: 1) What is the relationship or what are the common elements between Capital (or capitalism) and religion? 2) The influence and contributions of Feuerbach's critique of religion to the critique of political economy are present only in the works of the “young Marx”, or, they would also be present in his works of theoretical maturity, like Capital, for example? We also need to ask ourselves about Marx and Feuerbach: the criticism presented by Marx in relation to Feuerbach, as in his famous “Theses on Feuerbach”, for example, would represent, in essence, an “epistemological rupture” of Marx in relation to Feuerbach's critique or would it actually represent a complementation and development of Feuerbach's positions? 3) What are the similarities and differences between modern political economy and theology? Finally, we asked ourselves if we could say that capitalism, in addition to corresponding to a specific and historical mode of production, can also be considered a type of religion? In this sense, the present work seeks to compare the principles that give rise to religion and religious idolatry with the principles that give rise to idolatry or fetishism of merchandise, the State and, finally, capital. Therefore, we intend to highlight the function that metaphysical-theological assumptions have in the process of reproduction and legitimization of capital, seeking to explore, furthermore, the critical potential that theological metaphors assume in the work of Karl Marx. The theses we defend here are that: 1) Capitalism is not a religion, but rather a historical and transitory mode of production; However, modern political economy and, therefore, liberalism itself presents itself much more as a kind of “economic theology” than an “economic science” itself. 2) There is no epistemological break between Marx and his works and “theses of youth”; 3) In a general and particular, direct and indirect way, it is possible to observe how much the influence of Feuerbach's method and criticism of religion is decisive for the elaboration of the method and criticism developed by Marx, not only during his youth, but also in Capital (1867). 4) The structural analogy of capitalism with religion is an accurate diagnosis by Marx, which indicates the need for an adequate praxis, capable of facing the 'theological tricks and metaphysical subtleties' of capital.